Break the rules, save the records: human rights archives and the search for justice in East Timor - Robinson, Geoffrey (Archival Science, 2014)
How do distinctive historical experiences and political regimes shape human rights archives? How do those archives and those experiences in turn influence the way painful pasts are remembered or forgotten? And what can historical accounts tell us about the wisdom of prevailing norms and practices regarding the management and control of human rights records? This paper explores these questions through a close analysis of the history and politics of the principal archive documenting human rights abuse in East Timor. It underscores the work of archival studies scholars who argue that human rights archives are always in some degree shaped by the historical and political context in which they emerge and that conflicts over matters of content, mandate, and rules of access are virtually inevitable. Noting that such conflicts typically pit political authorities against victims and their advocates, it argues that successful human rights archival programs hinge critically on sensitive historical and political analysis and that, under certain conditions, human rights archivists should play a more active role in facilitating the pursuit of justice for victims of human rights abuse. It also makes the case for a move away from large, state-controlled archives toward multiple, smaller archives with varied mandates. Finally, it proposes the adoption of a new hierarchy of interest in the management of archives; away from the long-accepted principles of national sovereignty and inalienability, and in the direction of access to the survivors of human rights violations and their advocates.
Keywords: A&DwP website; Archives; East Timor; Human rights; Inalienability; Justice; National interest; Records; Secrecy; Security; Timor Leste; Truth commissions